특허권침해에서 손해배상책임에 대한 입증책임분배에 관한 연구 - 왕소려; Wang Xiao Li (공공정책연구, 2018)
중국은 특허법 및 그에 관한 법률에서 주로 특허권자의 실제 손실, 권리침해자의 권리침해로 이익, 로열티의 적정배수 및 법정배상 등 특허침해 배상액의 확정방법을 규정하고 있다. 그러나 실제 사법 적용에서 법정 배상이 압도적으로 우세한 것은 초기 입법취지와는 거리가 멀다. 그 원인은 특허 침해에 대한 손해배상액을 확정할 때 현행 중국 민사입증책임배분제도에 따라 특허권자가 과도한 증명책임을 지기 때문에, 특허권자가 실제 자신의 손해를 증명할 때 혹은 권리침해자가 얻은 이익이 합리적인 허락이 있을 경우에 증거를 제시하기 어려워 법원의 인가를 받지 못하면, 법정배상 방식을 통해 법관이 사건의 구체적인 상황에 근거하여 확정할 수밖에 없다. 이 논문에서는 특허침해 손해 배상 속에서 중국이 적용하는 전통 민사 증명책임 분배체계를 적용이 어렵다는 점을 분석하고, 중국에서 새로운 특허침해배상 입증책임배분체계의 필요성을 설명하고, 결국 선진제국의 사례를 참고하여 중국에 적용된 새로운 특허침해배상책임배분체계를 구축하고자 한다. 특히 입증책임분배의 일반적인 원칙을 준수하는 범위 내에서, 특허권자의 증명 책임을 적당히 경감하여, 특허권자의 이익을 더욱 잘 보호하고 특허침해 행위를 단속하고자 한다. Chinese patent law and relative legislations mainly stipulate actual losses obliges suffered, profits infringers get, reasonable times of royalty fees and ascertaining methods of indemnity amount for patent infringement damages including legal compensation. However, in the process of practical judicial applications, legal compensation has an absolute predominance, which is far away from legislators’ original intention. Why could this happen? The reason is that patentees have overburden the obligation of proof at the time of ascertaining indemnity amount of patent infringement damages in accordance with Chinese current distributing system of civil proof, resulting in patentees could not get affirmations from the court because they could barely provide evidences to prove actual losses they suffered, profits infringers get or even their reasonable royalty fees, which causes them to seek for a method of legal compensation where judges can ascertain on the basis of cases. This paper will elaborate the necessity of constructing a new distribution system of proof burden for patent infringement damages in China by means of analyzing difficulties in applying Chinese traditional distribution system of civil proof to patent infringement damages cases. The paper will also construct a new Chinese distribution system of proof burden for patent infringement damages on the basis of learning from others, expecting to mitigate patentees’ burden of proof in the context of complying with general distribution rules of burden of proof, so as to protect patent rights in a better way and take a tougher line against patent infringements. Key words: patent infringements, amount ascertain of damages, burden of proof and distribution systems.